Physicochemical Properties of Whole and Fresh Cut Durian (Durio Zibethinus) Stored At Ambient and Refrigerated Temperatures - Voon, Yit Yang (2008)
This study reports chemical changes occurring in the pulp of both whole and minimally processed (MP) durian (Durio zibethinus) stored at ambient and refrigerated temperatures. In the first part of this study, the pH, total soluble solids, titratable acidity, sugars, organic acids, flavour compounds and sensory properties of five Malaysian durian cultivars (‘D2’, ‘D24’, ‘MDUR78’, ‘D101’ and ‘Chuk’) were determined. There were significant differences in physicochemical characteristics among the cultivars. Analysis using solid-phase microextraction (SPME) coupled to gas chromatography- time of flight mass spectrometry (GC-TOFMS) revealed a total of 22 esters, 14 sulphur compounds, 7 alcohols, 3 aldehydes and 1 ketone in the pulp of the 5 durian cultivars. Sensory properties of four durian cultivars were compared. Twelve descriptors (sweet, fruity, sulphury, alcohol, nutty and green aroma, surface color, sweetness, bitterness, stickiness, moistness and overall aftertaste) were generated. A strong correlation was observed between sensory properties, flavour compounds and physicochemical characteristics of the fruit. In the second part of this study, activities of four cell wall hydrolases, pectinmethylesterase (PME), polygalacturonase (PG), cellulase and β-galactosidase (β-Gal) and physicochemical changes of ripen whole durian fruit (cultivar D24 and an accession from Kampung Bentong, Pahang) stored at 28 + 1 °C (RH 60-80%) for 4 days, were investigated. During storage, significant interaction effect of ‘accession x day of storage’ on weight loss, glucose content, PG and PME enzymes activities were observed. Weight loss increased linearly with an average weight loss of 3.9 and 4.9% per day for durian kampung and D24 respectively. The softer texture observed in the Kampung Bentong accession as compared to the D24, corresponded to its higher PG and cellulase activity. Transmission electron microscopy observations showed middle lamella dissolution and loss of intercellular materials in Kampung Bentong accession after 4 days of storage but not in the D24. The effect of storage temperature on the changes in the physicochemical, microbial and sensory quality of MP durian cultivar D24 was then determined at 28+1 oC for 3 days and 4+2 oC for 35 days. Around 400 g pulp was placed on a polystyrene tray and wrapped with LDPE film for storage. At 28+1 oC, the pulp retained its colour but softened rapidly after 24 h of storage and became acidic (pH 4.71) after 2 days of storage due to the formation of citric, succinic, acetic and lactic acids. Titratable acidity of the pulp that increased significantly after 2 days of storage was correlated to the decrease in pH. Sucrose decreased concomitantly with an increase in glucose and fructose concentrations during storage. For pulp stored at 4+2 oC, no noticeable changes in pH were observed. After 1 week of storage, there was a progressive increase in glucose, fructose and sucrose concentration with concomitant increase in total soluble solids. The firmness increased significantly at the end of storage. The organic acid content remained constant throughout the storage period with a slight increase in tartaric acid. Titratable acidity of the pulp decreased significantly after one-week storage and remained constant thereafter. The MP durian fruit could be kept at 4+2 oC for 14 days with acceptable microbiological quality and without development of off-odour. At ambient temperature, MP durian could only be stored for 1 day, after which the pulp became acidic. The volatile flavour compounds and sensory attributes of MP durian cultivar D24 stored at 4+2 ºC for 42 days were examined. The volatile compounds were extracted by SPME and analysed by GC-TOFMS. During storage of MP durian at 4+2 ºC, diminution of the major ester compounds was observed after 14 days of storage. All ester compounds decreased significantly after 7 days of storage except for ethyl acetate that decreased significantly after 2 weeks of storage. Ethanethiol, 1-propanethiol, and both isomers of 3,5-dimethyl 1,2,4-trithiolane decreased significantly after 7 days of storage. Total sulfur content of the pulp remained unchanged after 42 days of storage. However, sulfur notes perceived by panellists decreased gradually throughout storage. Quantitative Descriptive Analysis (QDA) was carried out using sixteen descriptors to describe the surface colour, odour, flavour and texture of pulp during storage. Results revealed that pulp could be stored for 21 days, after which off flavour developed and the green aroma became too intense and rendered the pulp unacceptable.